THE RELATIONSHIP OF LEARNING DISCIPLINE, PARENTAL ATTENTION, AND LEARNING MOTIVATION WITH MATHEMATICS LEARNING OUTCOMES OF STUDENTS IN VIII CLASS OF MTs NEGERI SUMBERAGUNG BANTUL - Choirunisa Desi Milasari P; Sumargiyani Sumargiyani (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2017)
Result of low mathematics learning associated with many factors. relationship of learning discipline, parental attention, and learning motivation are some of the factors related to the learning outcomes. Therefore, this study was conducted in order to determine whether or not a positive and significant between the relationship of learning discipline, parental attention, and learning motivation with mathematics learning outcomes of students in the VIII class of MTs Negeri Sumberagung Bantul in the even semester in Academic Year of 2015/2016. The population of this research was all students of class VIII MTs Negeri Sumberagung Bantul in the even semester of the academic year 2015/2016 consisting of 5 classes with the total number of 153 students. As a sample class was class VIII B consisting of 30 students by random sampling technique to the class. The data collection technique was performed by a method of testing and questionnaires. The test method used collection data on mathematics learning outcomes of students, whereas the questionnaire method used collection data learning discipline, parental attention, and learning motivation. Test data analysis requirements using the test for normality, independent, and the test for linearity. Data analysis for hypothesis testing using correlation analysis and linear regression analysis. The research result showed that there was a significant positive correlation between learning discipline, parental attention, and learning motivation with Fcount = 11,58570847 and Ftable = 2,98 in order to obtain Fcount > Ftable. Multiple correlation coefficient (R) of 0,7563508799 with a regression equation Â with a coefficient of determinationÂ  was (R2) 0,5720666536 and effective contribution X1 = 18,786%, X2= 15,582% and X3 =6,216%.